STUDENTS’ RESPONSE TO SMALL GROUP DISCUSSION TECHNIQUE IN TEACHING READING COMPREHENSION - Siti Ani; Rissa San Rizqiya (IKIP Siliwangi, 2024)
The purpose of this study was to determine the students' response towards the teaching of reading comprehension using small group discussion. This research involved seventh grade students of a junior high school in Bogor consisting of 28 students. The research used the descriptive qualitative method. To get the data, the researchers used the questionnaire. The assessment of the questionnaire grids were attention, relevance, confidence and satisfaction. The result showed that the average index score was 81.93 based on the interval chart 80% - 100% this score was very good. It could be concluded that students gave positive response to the use of small group discussion technique.